Por que (e por que não) rejeitar o monismo anômalo - Fischborn, Marcelo (2014)
Anomalous monism is a theory in the philosophy of mind put forth by Donald Davidson in the 1970s. Although influential at the time, it received numerous criticisms, and it is now widely rejected. The present Master s Dissertation argues for a revision of the reasons for which anomalous monism should be rejected. According to a well known objection in the literature, anomalous monism entails the thesis of property epiphenomenalism, and should be rejected because this consequence is unacceptable. It is proposed that this objection is inadequate in its two crucial steps. First, property epiphenomenalism does not seem to follow from anomalous monism, and, second, there seems to be no sufficient reason for a decisive rejection of property epiphenomenalism. Despite this, there are alternative reasons for rejecting anomalous monism, which concern the justification of the monist thesis. At least one of the premises Davidson takes to support it appears to be false, and, additionally, the very possibility of the monism at issue is threatened by problems in the ontology of events it assumes.